Proximal contact alterations between implant-supported restorations and adjacent teeth in the posterior region: A 3-month prospective study - Mehanna, Solange (J Clin Exp Dent, 2021)
BACKGROUND: Interproximal contact loss (ICL) is a multifactorial implant complication. The aims of this prospective clinical study were to evaluate proximal contact alterations between implant-supported fixed prostheses (IFPs) and adjacent teeth and to identify potential contributing factors. MATERIAL AND METHODS: This study was conducted from April to September 2019 at the Department of Prosthodontics. Forty-three patients (23 females and 20 males, age range 31-70) treated with 43 posterior IFPs were recruited for this study. All proximal contacts (64) were checked visually and radiographically. Proximal contact tightness (PCT) was clinically evaluated using dental floss and measured during removal of a calibrated 0.05 mm thick metal strip previously inserted into the proximal area. Mesial and distal PCT were measured at restoration insertion (T0), 1-month follow-up (T1), and 3-month follow-up (T2). ICL was assessed in relation to the patients’ age, gender, smoking habits, implant system, proximal contact position, jaw position and restoration type of the implant prostheses. The significance level was set at P value ≤ 0.05. RESULTS: The PCTs between fixed implant prostheses and adjacent teeth decreased significantly between T0 and T2. Restoration type affected the loss of interproximal contact at the mesial (free-end restorations; P = 0.008) and distal aspects (P< 0.001), whereas implant system affected only the distal aspects of the proximal contacts (P = 0.002). CONCLUSIONS: Proximal contact tightness between fixed implant prostheses and adjacent teeth decreased over the 3-month observation period. Contact loss between fixed implant prostheses and adjacent teeth may be influenced by restoration type and implant system. Key words:Adjacent teeth, dental implants, implant complication, implant fixed prostheses, interproximal contact loss, proximal contact strength, proximal contact tightness.